Tadrīs al-Mufāradāt li-Tatbīq Mihārat al-Kalām fī Madrasat al-Mu'allimīn al-Islāmiyah bī Ma'had Bayt al-Arqam Balong Jember - Muhammad Ardy Zaini (ALSINATUNA, 2017)
There are four skills in teaching Arabic : listening, speaking, reading, and writing. Among these four, speaking considered one of the most important objectives of learning foreign language. In order to speak properly, one must know the vocabulary and apply it in a sentence. The aims of this research is to describe the teaching of vocabulary to apply the speaking skill in the school of Islamic teachers in the Institute of Bait al Arqom Balong Jember. This study used qualitative approach. The data collection was taken trough observation, personal interview, history and documentation. The teaching of vocabulary to apply the speaking skill at the Islamic Teachers' School at the Institute of Bait Al Arqam Balong Jember has gone well in terms of planning (general objectives and specific objectives), implementation (materials, use of the teaching method and teaching aids), and evaluation (assessment and evaluation). This teaching is to apply the speaking skill in terms of conversation or dialogue and lecture.